Compositional Variation of PCBs, PAHs, and OCPs at Gas Phase and Size Segregated Particle Phase during Dust Incursion from the Saharan Desert in the Northwestern Anatolian Peninsula - S. Levent Kuzu (Advances in Meteorology)
A dust incursion occurred in Istanbul on 1 February 2015 from the Saharan Desert. During this episode, 938 μg·m−3 of TSP concentration was observed. TSP concentration was 64 μg·m−3 and 78 μg·m−3 on the following two days. Particles of 3 μm were dominant during the episode; however, particles < 0.49 μm were dominant after the episode. The averages of total (gas + particle) PCB, PAH, and OCP concentrations were 279 pg·m−3, 175 ng·m−3, and 589 pg·m−3, respectively. Tri-CBs were dominant in most of the samples. Flt and Phe had the highest contribution to PAH species. β-HCH and heptachlor had the highest share in terms of OCPs. Particle phase PCBs exhibited monomodal size distribution, whereas OCPs had bimodal size distribution. PAHs exhibited either monomodal or bimodal size distribution on different days. The mass median diameter of PAHs did not change significantly during different atmospheric conditions due to their local sources. Gas/particle partitioning of each pollutant was evaluated by plotting their subcooled vapor pressure against the partitioning coefficient. From 1 to 3 February, the slope of the regression line shifted close to −1, indicating that the least favorable conditions were present during dust incursion for an equilibrium state.